KUALITAS PRODUK DAN LAYANAN PURNA JUAL TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA PADA PT. SURACO JAYA ABADI MOTOR - Sigit Sugiarto; Edy Jumady (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This study aims to examine and to The Effect of Quality Product and After Sales Service on Purchase Decision of Yamaha Motorcycle, either simultaneously or partially at PT. Suraco Jaya Abadi Motor. The samples used in this research were 75 people with the method using Slovin formula with the number of respondents of 305 people. This research uses Multiple Regression Analysis. Based on the results of data analysis and hypothesis testing, this research shows that the F test results show that Product Quality and After Sales Service simultaneously influence the purchase decision. The result of t test also shows that the variable of product quality partially has positive and significant influence toward the purchase decision. Coefficient of determination of 0.327 which means that the role given by the variables combination of product quality and after sales service toward the purchase decision of 32.70% while the remaining 67.30% was influenced by the other factors which were not examined by the researcher.